Brazil as an economic superpower? : understanding Brazil's changing role in the global economy - Brainard, Lael; Martinez-Diaz, Leonardo, 1976- (Brookings Institution Press, 2009)
"Brazil is once again getting attention in the northern hemisphere--attention long overdue, given its huge and diverse population, its physical size and diversity, and its geopolitical and economic importance as the largest country in Latin America. Long seen as an economic backwater, Brazil now occupies key niches in energy, agriculture, service industries, even high technology markets. Yet the nation still struggles with endemic problems of inequality and with a traditional ambivalence toward deep integration with the world economy. Brookings gathered scholars and policymakers from Brazil, Europe, and the United States to examine the present state and likely future of Brazil's economy. Their findings can be found in Brazil as an Economic Superpower? The authors' analysis focuses particularly on five key topics: agribusiness, energy, trade, social investment, and multinational corporations. The net result is an invaluable analytical contribution and a provocative look into the future of our global economy and into the workings of one particularly important component of that system"--Provided by publisher